2013
DOI: 10.1086/673974
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Antimicrobial Susceptibility Trends across the United States

Abstract: Objective.Antimicrobial susceptibility patterns across US pediatric healthcare institutions are unknown. A national pooled pediatric antibiogram (1) identifies nationwide trends in antimicrobial resistance, (2) allows across-hospital benchmarking, and (3) provides guidance for empirical antimicrobial regimens for institutions unable to generate pediatric antibiograms.Methods.In January 2012, a request for submission of pediatric antibiograms between 2005 and 2011 was sent to 233 US hospitals. A summary antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 35 publications
0
25
1
Order By: Relevance
“…3,4,6,23 Before 2005, dramatic increases in rates of community-associated MRSA infection were reported, with most studies revealing oxacillin resistance in 40% to 60% of SSTIs. 16,24,25 The rate of rise of MRSA infections slowed by 2005-2006 and subsequently declined. 1-4, 12, 26, 27 A parallel decline in MSSA infections has not been consistently reported, with some authors noting stable rates of MSSA during the same time period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4,6,23 Before 2005, dramatic increases in rates of community-associated MRSA infection were reported, with most studies revealing oxacillin resistance in 40% to 60% of SSTIs. 16,24,25 The rate of rise of MRSA infections slowed by 2005-2006 and subsequently declined. 1-4, 12, 26, 27 A parallel decline in MSSA infections has not been consistently reported, with some authors noting stable rates of MSSA during the same time period.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have suggested that despite a high burden of S aureus disease in children, resistance to non-β-lactam antibiotics is relatively uncommon. 1,2,[14][15][16][17] Our study evaluates annual antimicrobial susceptibility trends of S aureus isolates from infections in pediatric patients receiving care in the Military Health System (MHS) treatment facilities from 2005 to 2014. Differences in antimicrobial susceptibility of S aureus between age groups, infection types, patient status (inpatient versus outpatient), and geographical region were examined.…”
mentioning
confidence: 99%
“…28 As expected, when the use of the fluoroquinolones (in particular levofloxacin) increased, the susceptibility of Gram-negative bacilli to ciprofloxacin and levofloxacin significantly decreased. 29 …”
Section: Resistancementioning
confidence: 99%
“…Our b-lactam and aminoglycoside antibiotic susceptibility percentages, however, appear consistent with a study evaluating antibiotic susceptibility data from 55 contributing institutions caring for children in the United States. 26 Second, although we did not find a benefit of combination therapy in a subgroup analysis of children who had ANCs #100 cells/mL or PRISM III scores $15, there were only 49 and 114 children in these categories, respectively, and we may have been unable to detect a difference in the clinical outcomes of children comparing combination therapy versus monotherapy, if a difference exists. Further prospective studies are needed to evaluate patients in these risk categories.…”
Section: Figurementioning
confidence: 61%
“…Similarly, aztreonam had 83% in vitro activity in a pediatric study of some 33 000 diverse-source Gram-negative isolates. 26 Patients who have an inability to tolerate penicillins may benefit from the routine addition of an aminoglycoside to aztreonam on an empirical basis. In contrast, monotherapy with ceftriaxone (when hospitalacquired Gram-negative infections are unlikely), piperacillin-tazobactam, cefepime, or meropenem will likely suffice.…”
Section: Discussionmentioning
confidence: 99%